Material Removal Mechanism of Green Machining on Powder Metallurgy Parts during Orthogonal Cutting - Dayong Yang; Longsheng Lu; Zhenping Wan (Advances in Materials Science and Engineering)
Due to its energy-saving and cost-reducing characteristics, a novel green machining technique for powder metallurgy (PM) parts is attracting increasing concern. Unlike in the traditional PM machining technique, in the PM green-machining method arranges, the processing operation is performed before sintering. Since the pristine PM compacts are relatively soft because it just bonds the particles together, direct cutting on pristine PM compacts is a tool-saving and cost-effective manufacturing technique and its cutting mechanism is different from that of both solid plastic metals and conventional brittle materials because of the special characteristics of a discontinuous material. The influences of cutting parameters on machined surface roughness are investigated by orthogonal cutting experiments. The results show that the machined surface roughness decreases with increasing cutting thickness and rounded cutting edge radius and slightly increases with increasing rake angle. It is suggested that these results are contrary to the long-held notions of machined surface roughness. Moreover, a geometric model illustrating the PM green-machining process was established to reveal the mechanism of material removal and machined surface formation. This model shows that the material removal of PM is composed of particle shearing deformation, peeling, and ploughing/extruding. Finally, this machining model was validated through observations of machined surface morphology and chip morphology.